2019
DOI: 10.26717/bjstr.2019.17.002987
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Human Neural Crest-Related Stem Cell Homing (hNCSCs homing) on the Mineralization of Newly Formed Alveolar Bone using an Allogen Bone Substitute

Abstract: The therapies to regenerate periimplant bone tissues have attracted lots of attention these years. Neural crest-related stem cells (NCSCs), a group of cells containing heterogeneous stem/progenitor cells, are capable of homing to injured tissues and participating in periimplant bone regeneration. The amplification of autologous NCSCs potential in homing for self-repair/regeneration, therefore, might be considered as an alternative therapy except for traditional cell transplantation. However, the knowledge of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…The results showed that LiCl activated canonical Wnt signaling and promoted the proliferation and odontogenic differentiation of hfNCCs, suggesting that hfNCCs may be a good candidate for tooth regeneration 117 . As adult tissue‐derived NCLSCs can undergo osteogenic differentiation in vitro, they are a promising cell source for bone regeneration 118,119 . NCLSCs isolated from excised human oral mucosa could generate spheres that were multipotent and capable of self‐renewal in vitro 118 .…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that LiCl activated canonical Wnt signaling and promoted the proliferation and odontogenic differentiation of hfNCCs, suggesting that hfNCCs may be a good candidate for tooth regeneration 117 . As adult tissue‐derived NCLSCs can undergo osteogenic differentiation in vitro, they are a promising cell source for bone regeneration 118,119 . NCLSCs isolated from excised human oral mucosa could generate spheres that were multipotent and capable of self‐renewal in vitro 118 .…”
Section: Introductionmentioning
confidence: 99%
“…The results show how spheroids and adherent cells; similar in morphology to neurospheres and resultant NC-SCs isolated from heterogeneous suspensions of NCCs 17,25 , can be derived from samples of mammalian skeletal muscle treated with both mechanical and enzymatic techniques. The handling and preparation of skeletal muscle-derived cells was performed analogous to the preparation of oral-derived NCSCs as detailed in publications of our research group [25][26][27]29,30 . Before addressing the hypothesis and research question of this project; data from this report and similar research must be considered to assess whether mechanical dissociation is a viable alternative to enzymatic digestion for the isolation of therapeutic stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Cultures were established from a varied cohort of rat tissue samples and grown, as monolayers, serum-free, and under sphere-aggregation conditions to induce and identify a NCSC-like phenotype. We have characterized oral-derived NCSC cultures from different tissue sources by immunocytochemistry and reverse transcription quantitative polymerase chain reaction in our earlier publications [25][26][27]29,30 . Here, we tried to handle and preparate skeletal muscle-derived cells performed analogous to the preparation of oral-derived NCSCs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations